CrowdAR: A Live Video Annotation Tool for Rapid Mapping. (2016) - Salisbury, Elliot; Stein, Sebastian; Ramchurn, Sarvapali
Abstract: Digital Humanitarians are a powerful and effective resource to analyse the vast amounts of data that disasters generate. Aerial vehicles are increasingly being used for gathering high resolution imagery of affected areas, but require a lot of effort to effectively analyse, typically taking days to complete. We introduce CrowdAR, a real-time crowdsourcing platform that tags live footage from aerial vehicles flown during disasters. CrowdAR enables the analysis of footage within minutes, can rapidly plot snippets of the video onto a map, and can reduce the cognitive load of pilots by augmenting their live video feed with crowd annotations.